EFL LEARNERS’ PERCEPTION TOWARDS THE IMPLEMENTATION OF DICTOCOMP IN ENGLISH WRITING CLASSROOM: English - Jaya Nur Iman; Nike Angraini; Desi Surayatika (Prodi Tadris Bahasa Inggris, 2023)
This research aimed at seeing whether or not the EFL learners had positive perception towards teaching English writing with dictocomp. An experimental research design which mainly concerned on the descriptive analysis was used. Eighteen students were selected purposively as the research sample. A close-ended questionnaire with 15 question items was used as a main instrument to see their feedback. The research findings revealed that the EFL learners’ learning motivation and confidence were exceedingly boosted. In addition, their English writing difficulties were slightly solved. Furthermore, their English writing performance had positive and significant development after being instructed with dictocomp. Another positive response was about the English writings aspects of the EFL learners were also well-improved. Thus, in concluding, the EFL learners had positive perception towards the implementation of dictocomp in English writing classroom.